Teaching-learning sequences: an approach based on learning demands for teaching Physics - Silvane Tortelli Guarrezi; Marcelo Paes de Barros; Dulce Ferreira da Silva (Pesquisa e Ensino, 2020)
This article describes the effect of a Teaching-Learning Sequence (TLS), based on the learning demand concept, in promoting students’ learning and in extend their analysis to wider physics concepts. It examines the written and oral arguments produced by first year high school students, in Sorriso, MT, during a complete PMTU developed in August 2019. The data used in this analysis was derived from written responses, audio and video recordings, and written field notes. The findings show that this TLS can be useful for promoting students’ argumentation and can potentially improve students` learning of physics concepts, shedding light on some strategies that have shown the potential to be applied in TLSs on different topics.